Empathic disequilibrium as a new framework for understanding individual differences in psychopathology - Shalev, Ido; Eran, Alal; Uzefovsky, Florina (Frontiers in Psychology, 2023)
Introduction Empathy is part of basic social cognition and is central to everyday interactions. Indeed, emotional and cognitive empathy deficits are related to various psychopathologies, yet the links reported have been inconsistent. Thus, the mechanism underlying these inconsistent links is poorly understood. At least a partial answer may lie in that the dependency between cognitive and emotional empathy has been overlooked. Here, we examined the (dis)equilibrium between emotional and cognitive empathy and how it relates to individual differences in clinical traits. We further examined a possible mediator of these links—emotional reactivity. Methods Participants (N = 425) from the general population reported on their empathy, emotional reactivity, autistic traits, psychopathic tendencies, and symptoms of depression and anxiety. Results Beyond empathy, both extremes of empathic disequilibrium were associated with various features of clinical conditions; Higher emotional relative to cognitive empathy was related to the social domain of autism and anxiety, while higher cognitive relative to emotional empathy was related to the non-social domain of autism, depression symptoms, and psychopathic tendencies. The associations with autistic traits, anxiety, and psychopathic tendencies were mediated by emotional reactivity. Discussion Our findings suggest a new framework for understanding how individual variability in empathy is expressed in various psychopathologies.